Clinical approach in PIPj flexion contracture conservative treatment: our experience - Tocco, Silvio; Pedrazzini, Alessio; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2016)
Proximal interphalangeal joint (PIPj) flexion contractures are a common clinical problem seen by hand therapists and orthopaedic surgeons after various types of injury to the finger. Conservative treatment is preferable over surgery but a variety of pre-fabricated and custom-made orthoses have been proposed in the literature. The aim of the present paper is to share our 15 year experience in treating PIPj flexion contractures using 2 different custom-fabricated orthoses and the exercise regimen used to preserve maximal PIPj passive and active extension obtained through the orthotic intervention. Synthetic serial casting and static-progressive splinting are in our opinion the best choices to treat even the most resilient PIPj flexion contractures as they both offer maximal Total-End-Range-Time (TERT) and minimize functional impediment of the hand while they are in use. Either approach offers advantages and set-backs that need to be discussed with the patient once his or her functional demands and ADL/leisure limitations have been identified.